The Green Knight [videorecording (DVD)] - Lowery, David; Lowery, David; Patel, Dev, 1990-; Vikander, Alicia, 1988-; Edgerton, Joel, 1974-; Harris, Sean, 1966- (Lionsgate, 2021)
A fantasy adventure based on the Arthurian legend, the film tells the story of Sir Gawain, King Arthur's headstrong nephew, who embarks on a quest to confront the eponymous knight, a gigantic tree-like creature.